Analysis of The Implementation of The Independent Learning Curriculum in Physical Education, Sports and Health Subjects in Tambakromo District - mahbubi, iqbal syarifuddin mahbubi; Hermawan Pamot Raharjo; Donny Wira Yudha Kusuma (Universitas Negeri Semarang, 2025)
This study analyzes the implementation of the Independent Learning Curriculum in Physical Education, Sports, and Health (PJOK) subjects in elementary schools in Tambakromo District. Using a qualitative approach, this study involved 11 PJOK teachers as respondents. Data were collected through interviews, observations, and documentation. Results show that the curriculum has been implemented with learning plans tailored to students' needs, student-centered execution, and both formative and summative assessments. The main challenges include limited facilities and infrastructure and the application of differentiated learning. This study emphasizes the importance of ongoing support to improve the effectiveness of curriculum implementation.